Perspectives of hearing impaired students in higher education in the time of COVID-19 - Vásquez León, Shirley Mirella (2022)
The research aims to relate the characteristics of the management and organizational capacity of the Peruvian university with the level of educational inclusion of students with hearing disabilities. A cross-sectional correlational design was used and a descriptive and inferential statistical analysis was carried out of the results of the Inclusive Educational Environment (3E + I) questionnaire, which was applied to a random sample of two groups of students (a group with disabilities and another without disabilities). The instrument was validated by means of a previous pilot test whose Cronbach’s alpha reliability index was 0.920. The results showed an inverse negative correlation between the perceptions of the clusters. Also, students with hearing disabilities identified a lower prevalence of educational inclusion in the university in relation to non-disabled students. The main causal factor of this situation in the university is a weak organizational and formative function of strategies to improve the development of the sociocultural competence of students in general. In this study it is concluded that the Peruvian university does not carry out an effective management of educational inclusion of students with hearing disabilities due to the lack of organization and implementation of intervention procedures aimed at people with disabilities such as hearing.